Dendritic cell-natural killer cell cross-talk modulates T cell activation in response to influenza A viral infection - Abigail G. Harvey; Athens M. Graves; Chandana K. Uppalapati; Saoirse M. Matthews; Stephanie Rosenberg; Emma G. Parent; Madison H. Fagerlie; Jack Guinan; Brina S. Lopez; Lisa M. Kronstad (Frontiers in Immunology, 2022)
Influenza viruses lead to substantial morbidity and mortality including ~3-5 million cases of severe illness and ~290,000-650,000 deaths annually. One of the major hurdles regarding influenza vaccine efficacy is generating a durable, robust cellular immune response. Appropriate stimulation of the innate immune system is key to generating cellular immunity. Cross-talk between innate dendritic cells (DC) and natural killer (NK) cells plays a key role in activating virus-specific T cells, yet the mechanisms used by influenza A viruses (IAV) to govern this process remain incompletely understood. Here, we used an ex vivo autologous human primary immune cell culture system to evaluate the impact of DC-NK cell cross-talk and subsequent naïve T cell activation at steady-state and after exposure to genetically distinct IAV strains–A/California/07/2009 (H1N1) and A/Victoria/361/2011 (H3N2). Using flow cytometry, we found that exposure of DCs to IAV in co-culture with NK cells led to a decreased frequency of CD83+ and CD86+ cells on DCs and an increased frequency of HLA-DR+ on both DCs and NK cells. We then assessed the outcome of DC-NK cell cross-talk on T cell activation. At steady-state, DC-NK cell cross-talk increased pan T cell CD69 and CD25 expression while exposure to either IAV strain reduced pan T cell CD25 expression and suppressed CD4+ and CD8+ T cell IFN-γ and TNF production, following chemical stimulation with PMA/Ionomycin. Moreover, exposure to A/Victoria/361/2011 elicited lower IFN-γ production by CD4+ and CD8+ T cells compared with A/California/07/2009. Overall, our results indicate a role for DC-NK cell cross-talk in T cell priming in the context of influenza infection, informing the immunological mechanisms that could be manipulated for the next generation of influenza vaccines or immunotherapeutics.